2020
DOI: 10.3390/su12145847
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Localization in the Arab Gulf Countries: How Do Organizations Socialize the Members of a Powerful Minority?

Abstract: This paper addresses a key social–cultural aspect of sustainability in the Gulf region: Workforce localization (WL). Our research objective is to empirically explore organizational socialization (OS) practices in the context of WL in the United Arab Emirates (UAE), where National Citizens (NCs) are a powerful minority in the workforce. This research adopts a qualitative methodology, using semi-structured interviews with managers in charge of the WL program in 14 organizations in the UAE, across different indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Thus, an in-depth analysis was inconclusive as to female leaders' perceptions of their organizations' diversity management policies. There was no significant evidence to support Waxin et al. ’s (2020) study that women's performance evaluations were impacted negatively because of gender stereotyping by others, women or men and by a woman's own perception of her leadership abilities.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, an in-depth analysis was inconclusive as to female leaders' perceptions of their organizations' diversity management policies. There was no significant evidence to support Waxin et al. ’s (2020) study that women's performance evaluations were impacted negatively because of gender stereotyping by others, women or men and by a woman's own perception of her leadership abilities.…”
Section: Discussionmentioning
confidence: 69%
“…Furthermore, the most important person to influence women's careers was their line manager, who was usually a man, and, therefore, being a woman put her at a disadvantage at work because of the negative gender stereotype held by those direct managers (Alfred and Wen, 2015). Waxin et al (2020) also found performance evaluations of women were impacted by this gender stereotyping by others, women or men, as well as by a woman's perception of her own ability to lead. The ensuing fallout from such gender stereotyping and gendered cultural values restricts a woman's experience, e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brunei has significantly reduced the practice of outsourcing foreign workers by 18.3% (13,600 persons) in 2020, primarily due to the COVID-19 travel restrictions into the country and increased local workforce participation rate, especially in jobs previously dominated by migrants, such as the food and retail sectors (Department of Planning and Statistics, 2020; Centre for Strategic and Policy Studies, 2022). To address the inflow of foreign workers, the Brunei government used a similar strategy as the Arab Gulf nations, implementing a new labour policy incorporating the localisation of the workforce to minimise reliance on migrants and provide more job security for locals (Waxin et al. , 2020; Chian, 2020).…”
Section: Discussion Of Strengthsmentioning
confidence: 99%
“…workforce to minimise reliance on migrants and provide more job security for locals (Waxin et al, 2020;Chian, 2020).…”
Section: Future Of Workmentioning
confidence: 99%
“…Against this backdrop, Emiratization is often implemented by a foreign workforce (Elbanna, 2021), thus possibly creating tensions between locals and expatriates. In other words, employing locals is perceived as an investment to the country's economic prosperity and stability, whereas utilizing a foreign workforce seems to be more of transactional nature (Waxin, Kumra, & Zhao, 2020).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%